2004
DOI: 10.1002/cncr.20373
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive factors and risk of breast carcinoma in a study of white and African‐American women

Abstract: BACKGROUNDFew studies have investigated the association between reproductive factors and the risk of breast carcinoma among African‐American women. The authors assessed whether the number of full‐term pregnancies, age at first full‐term pregnancy, and total duration of breastfeeding were associated with similar relative risk estimates in white and African‐American women in a large multicenter, population‐based case–control study of breast carcinoma.METHODSCase patients were 4567 women (2950 white women and 161… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 34 publications
8
48
1
3
Order By: Relevance
“…We recently confirmed these findings in the Women's Contraceptive and Reproductive Experiences (CARE) Study and showed that these effects are similar in African-American and White women (Ursin et al, 2004).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…We recently confirmed these findings in the Women's Contraceptive and Reproductive Experiences (CARE) Study and showed that these effects are similar in African-American and White women (Ursin et al, 2004).…”
supporting
confidence: 53%
“…Our recent evaluation of reproductive factors from the CARE study (Ursin et al, 2004) found that the effects of reproductive factors were in general very similar in African-American and White women. In particular, parity and lactation had similar protective effects in the two racial groups.…”
Section: Discussionmentioning
confidence: 96%
“…There is some evidence to suggest that, unlike the protective effect of pregnancy on breast cancer risk among women after age 45, early childbearing and higher birth rate observed among black women could increase the likelihood of higher incidence of premenopausal breast cancer [28][29][30] . Moreover, among younger black women, multiparity 31 coupled with lower likelihood of lactation and shorter duration of lactation 32 may also contribute to a higher incidence rate. The reduction in modifiable risk factors including, hormone replace therapy, alcohol consumption, physical activity, and duration of breast-feeding, could substantially reduce breast cancer incidence 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive history is the strongest and most consistent risk factor outside of genetic background and age (McPherson et al 2000, Harris et al 1992, Kelsey & Gammon 1991, Althuis et al 2004, Ursin et al 2004. Early menarche, late menopause, parity, and late age of first pregnancy are each independent risk factors.…”
Section: Epidemiological Considerationsmentioning
confidence: 99%